MLTI-10. ESTABLISHMENT OF A MULTIDISCIPLINARY BRAIN METASTASIS CLINIC TO FACILITATE PATIENT-CENTERED CARE AND COORDINATED RESEARCH. (12th August 2019) - Li, Jing; Lang, Frederick F; Guha-Thakurta, Nandita; Weinberg, Jeffrey S; Rao, Ganesh; Heimberger, Amy; Ferguson, Sherise; Prabhu, Sujit; Sawaya, Raymond; Yeboa, Debra N; McAleer, Mary Frances; Chung, Caroline; et al.
Abstract: BACKGROUND: 30% cancer patients develop brain metastases (BM), reflected by 1600 BM patients treated at MD Anderson Cancer Center annually. With advances in systemic therapy and extracranial disease control, BM is a growing challenge. Multi-disciplinary BM management is critical and complex requiring coordination of multiple oncology sub-specialties. There is limited data on pragmatic clinic models to streamline and advance care. METHODS: Recognizing deficiency in BM treatment and research, a steering committee was formed at MDACC to establish an interdisciplinary BM clinic (BMC), with a multi-disciplinary BM research retreat held in 2016. The goal of BMC was to centralize patient referrals, improve patient outcomes and experience, and advance research by developing clinical trials and biomarker discovery programs. Meetings were held to address BMC format, workflow, EMR integration, data collection infrastructure, and staffing model. RESULTS: MDACC BMC clinic opened in 01/2019 with two half-day clinics staffed by neurosurgery, neuro-radiation oncology, neuro-radiology and medical/neuro oncology. A dedicated advanced practice provider screens the referrals according to a well-developed algorithm. A multidisciplinary conference is held immediately before each clinic where patient images are reviewed, cases are discussed and consensus recommendations are developed. The treatment plan and follow up appointments are arranged at the completion of the clinic visit to expedite care. 50 patients have been seen with excellent patient satisfaction response and reduced time to treatment. 20% patients had major change in treatment plan following multi-disciplinary evaluation. Additional efforts to develop a central BM database along with clinical and translational research programs are on-going. CONCLUSIONS: Establishment of a multi-disciplinary BMC to facilitate care and centralize research programs addresses a critical need for coordinated patient-centered BM management. This endeavor has enhanced patient experience through multi-specialty collaboration. Our program demonstrates the feasibility and effectiveness of a dedicated BMC in the treatment of this complex patient population.